(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The weakness of knowledge about linseed varieties and its growing features depending on genotype prevent linseed growing and seed marketing in Lithuania. The linseed varieties in Lithuania didn’t achieve yield promised in the variety description. The aim of our investigations was to establish the influence of linseed genotype on the plant productivity, agrotechnical and biological characteristic and seed quality. Nine linseed varieties: Helmi, Szafir, Symphonia, Blue Chip, Lirina, Olinette, Lu-5, Gold Merchant and Flanders were tested in year 2008. As the result of our investigations, the linseed variety Symphonia, with best productivity is recommended to grow and multiple in Lithuania.